Effect of sucrose and plant growth regulators on callogenesis and preliminary secondary metabolic of different explant Myrmecodia tuberosa - YANTI PUSPITA SARI; EKO KUSUMAWATI; CHAIRUL SALEH; WAWAN KUSTIAWAN; SUKARTINGSIH SUKARTINGSIH (Smujo International, 2018)
Sari YP, Kusumawati E, Saleh C, Kustiawan W, Sukartingsih. 2018. Effect of sucrose on callogenesis and preliminary secondary metabolic of different explant (Myrmecodia tuberosa). Nusantara Bioscience 10: 183-192. Myrmecodia tuberosa Jack is a medicinal plant that contains bioactive compounds, such as flavonoids, tannins, tocopherols, phenols, and an abundance of minerals, that are useful as antioxidants. With the constant increases in popularity of the medicinal plant, the M. tuberosa is threatened by extinction if over-exploitation continues. Thus, the effort to conserve this plant is vital. Tissue culture is an alternative method to conserve and produce active compounds that are similar to those of the native ant nest plant with callus. The addition of certain compounds such as sucrose can affect the secondary metabolite content through in vitro plant or callus. The aim of this research was to find the explant sources (cotyledon, stem, tuber, and root), determine the best growth regulator to produce the callus, and evaluate the optimum sucrose concentration to enhance secondary metabolite production of the callus. The results showed that callus was obtained from all explant sources and all growth regulators. The best callus that was marked by a friable green and yellowish green callus was provided by cotyledon with the growth regulator of 2 mg?L-1 of 2.4-dichlorophenoxyacetic acid (2.4-D) and 2 mg?L-1 of kinetin. Calli treated with 30 g of sucrose resulted in the best secondary metabolites, containing alkaloids, phenols, flavonoids, saponins, and steroids.